2006
DOI: 10.1210/en.2005-0731
|View full text |Cite
|
Sign up to set email alerts
|

Liver Triglyceride Secretion and Lipid Oxidative Metabolism Are Rapidly Altered by Leptin in Vivo

Abstract: Leptin has potent lipid-lowering effects in peripheral tissues and plasma that are proposed to be important for the prevention of cellular lipotoxicity and insulin resistance. The current study addressed in vivo the effects of acute leptin delivery on liver triglyceride (TG) metabolism, the consequence of hepatic leptin action on whole-body TG homeostasis, and the mechanisms of leptin action. A 120-min iv leptin infusion (plasma leptin, approximately 14 ng/ml) decreased liver TG levels (53 +/- 3%; P = 0.001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
90
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 42 publications
(71 reference statements)
10
90
2
1
Order By: Relevance
“…Consistent with the literature, 14,32 our data do support the fact that direct leptin action on the liver plays an antisteatotic role, but the level of hepatic steatosis in Lepr flox/flox AlbCreþ mice was not as severe as in livers of db/db mice. Furthermore, unlike db/db mice with a global loss of leptin signaling, lean mice with a liver-specific loss of leptin signaling have normal total fasting plasma triglycerides and cholesterol levels.…”
Section: Leprsupporting
confidence: 93%
“…Consistent with the literature, 14,32 our data do support the fact that direct leptin action on the liver plays an antisteatotic role, but the level of hepatic steatosis in Lepr flox/flox AlbCreþ mice was not as severe as in livers of db/db mice. Furthermore, unlike db/db mice with a global loss of leptin signaling, lean mice with a liver-specific loss of leptin signaling have normal total fasting plasma triglycerides and cholesterol levels.…”
Section: Leprsupporting
confidence: 93%
“…PAS-leptin shifted fuel selection towards lipid oxidation. This could have been mediated either by direct stimulation of lipid metabolism or by an inhibitory effect on energy intake [28][29][30]. Indeed, the latter phenomenon was confirmed in both cohorts used in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, leptin has been shown to increase hepatic fatty acid oxidation and plasma triglyceride as well as reduce triglyceride secretion into plasma [55,56]. However, this study found minimal correlations between leptin and lipid profiles.…”
contrasting
confidence: 66%